High molecular weight amyloid β1‐42 oligomers induce neurotoxicity via plasma membrane damage. Issue 8 (13th May 2019) - Yasumoto, Taro; Takamura, Yusaku; Tsuji, Mayumi; Watanabe‐Nakayama, Takahiro; Imamura, Keiko; Inoue, Haruhisa; Nakamura, Shiro; Inoue, Tomio; Kimura, Atsushi; Yano, Satoshi; Nishijo, Hisao; Kiuchi, Yuji; et al.
ABSTRACT: Amyloid β‐protein (Aβ) molecules tend to aggregate and subsequently form low MW (LMW) oligomers, high MW (HMW) aggregates such as protofibrils, and ultimately fibrils. These Aβ species can generally form amyloid plaques implicated in the neurodegeneration of Alzheimer disease (AD), but therapies designed to reduce plaque load have not demonstrated clinical efficacy. Recent evidence implicates amyloid oligomers in AD neuropathology, but the precise mechanisms are uncertain. We examined the mechanisms of neuronal dysfunction from HMW‐Aβ1‐42 exposure by measuring membrane integrity, reactive oxygen species (ROS) generation, membrane lipid peroxidation, membrane fluidity, intracellular calcium regulation, passive membrane electrophysiological properties, and long‐term potentiation (LTP). HMW‐Aβ1‐42 disturbed membrane integrity by inducing ROS generation and lipid peroxidation, resulting in decreased membrane fluidity, intracellular calcium dysregulation, depolarization, and impaired LTP. The damaging effects of HMW‐Aβ1‐42 were significantly greater than those of LMW‐Aβ1‐42 Therapeutic reduction of HMW‐Aβ1‐42 may prevent AD progression by ameliorating direct neuronal membrane damage.—Yasumoto, T., Takamura, Y., Tsuji, M., Watanabe‐Nakayama, T., Imamura, K., Inoue, H., Nakamura, S., Inoue, T., Kimura, A., Yano, S., Nishijo, H., Kiuchi, Y., Teplow, D. B., Ono, K. High molecular weight amyloid β1‐42 oligomers induce neurotoxicity via plasma membrane damage. FASEB J. 33, 9220–9234 (2019). www.fasebj.org